(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
The focus of this paper is Paul Ricour’s philosophy of political ethics; addressing the phenomenon of injustice towards others in practical politics in Indonesia. The author reviews it using a text analysis method based on the book Oneself as Another. In the book, Ricoeur defines political ethics as "living well together with and for others in just institutions". This means that a good life is not only directed to oneself but also directed to others. Who else? Others refer to people who are marginalized socially, culturally and politically. For example, in a cultural context, it is racism or discrimination against the Papuan people. They are often referred to as the monkey nation. The term monkey is understood as a form of denial of their identity as humans. They were eliminated from the house of Indonesia which is under the umbrella of Pancasila. Others also appear on the issue of majority and minority, especially regarding religion. The position of the other as an object shows the decadence of moral ethics in practical political life in Indonesia. According to Ricoeur self and others must be in a symmetrical relationship to achieve mutual prosperity (bonum commune).